PENGARUH PERSEPSI PUBLIK DALAM WEB TERHADAP IDENTITAS PERUSAHAAN (KASUS INDUSTRI PENERBANGAN NASIONAL) - Jeffry Sudirja (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
This study aims to determine the effect of corporate identity displayed on airlines websites simultaneously on public perceptions of national airlines in Indonesia. The theory used in this study is the perception theory related to the world of service industry. The approach used in this study is a survey and the type of research is quantitative descriptive. The technique of collecting data uses as many questionnaires 200 respondents. To test the hypothesis, correlation analysis is used. The results of the study show that the corporate identity is displayed on the website has a significant effect on public perception for national airlines in Indonesia. The dominant variable that has a significant influence is reliability.